COVID-19 and Quarantine, a Catalyst for Ageism - Barth, Nathalie; Guyot, Jessica; Fraser, Sarah Anne; Lagacé, Martine; Adam, Stéphane; Gouttefarde, Pauline; Goethals, Luc; Bechard, Lauren; Bongue, Bienvenu; Fundenberger, Hervé; Célarier, Thomas (Frontiers in Public Health, 2021)
In February 2021, France had more than 76,000 deaths due to COVID-19 and older adults were heavily affected. Most measures taken to reduce the impact of COVID-19 (quarantine, visit ban in nursing home, etc.) significantly influenced the lives of older adults. Yet they were rarely consulted about their implementation. Exclusion of and discrimination against older adults has been accentuated during the COVID-19 pandemic. While many articles discussing COVID-19 also mention ageism, few actually incorporate the perspectives and opinions of older adults. Our research aims to assess the ageism experienced by older adults during the COVID-19 pandemic. We conducted interviews with older adults (63-92 years, mean age=76 years) in an urban area of France. Participants reported experiencing more ageism during the COVID-19 pandemic, including hostile and benevolent ageism from older adults’ families. Despite reports of experiencing ageist attitudes and behaviours from others, however, older adults also identified positive signs of intergenerational solidarity during this COVID-19 crisis.